ANALISA PEMELIHARAAN KOREKTIF ALAT ULTRASONOGRAFI (USG) GE HEALTH/LOGIC BOOK DI RSUD SIDIKALANG - Matanari, Amrul Aswadi; Situmorang, Harold; Abdillah, Khairil (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2023)
Research on Corrective Maintenance Analysis on Ultrasound (Ultrasound) was researched at a SIDIKALANG Hospital. The upkeep of medical equipment is crucial, as it plays a significant role in prolonging the lifespan of the devices and ensuring their operational efficacy in accordance with established specifications. Corrective maintenance refers to the repair processes undertaken for equipment that has sustained damage, which may involve the use of spare parts or not. The primary objective of this type of maintenance is to restore the damaged equipment to a functional state that is appropriate for use and ready for operational deployment. The purpose of the research is to find out the maintenance of Ultrasound equipment (USG) at SIDIKALANG Hospital. Methods used: Observation and Qualitative. The results of the study were damage to the probe, cable problems (disconnected), problems with the acoustic lens of the probe, and damage to the connector. And the solution to the damage is measured and tested on the probe/transducer, soldering or replacing the cable, replacing the acoustic lens or replacing the probe, and replacing the connector (which is carried out at Sidikalang Hospital).